American College of Medical Genetics and Genomics ACT Sheets Are a Vital Resource for State Newborn Screening Programs - Virginia Sack; Sara Etienne; Grace Beal; Sarah Bradley; Michele Caggana (International Journal of Neonatal Screening, 2024)
The American College of Medical Genetics and Genomics (ACMG) and the National Coordinating Center for the Regional Genetics Networks (NCC)-developed ACT sheets are a vital resource for state newborn screening (NBS) programs. They allow NBS programs to be able to provide up-to-date, just-in-time disorder information to primary care providers (PCPs). Their continued availability is necessary to ensure that all babies identified by newborn screening receive appropriate evaluation and care.